Effect of Strontium on the Structural, Optical, and Magnetic Properties of Bi(1-x)SrxFeO3 - Jebur, Khalid H. (Journal of Petroleum Research and Studies, 2025)
The composite Bi(1-x) SrxFeO3 (x = 0.0, 0.2, 0.4, 0.6, 0.8) was produced via solid-state reaction technique at 850 °C, in order to evaluate how strontium affects the structure. X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive ‎X-ray spectroscopy (EDX), magnetic analysis (VSM), and band gap energy measurements ‎were performed by UV- visible spectroscopy. ‏The results obtained are the formation of ‎crystalline materials of rhombohedral surfaces and change to the pseudocubic phase ‎at x = 0.4. The particle size declines ‎from 36.5 nm up to 17 nm for the pure sample in BSFO. The strontium Sr+2 caused an increase in ‎Remnant magnetization (Mr) and coercive field (Hc), which lead to the magnetization ‎development of BiFeO3, UV- visible spectroscopy used to‏ ‏calculate the direct optical ‎band gap of all samples had its value on the order of 2.4 to 2.9 eV.